The Impact of Human Resources Aspects in Supporting Readiness for Change at PT Pertamina (Persero) - Moresia Raditya; Hafiz Rahman; Rahmi Fahmy (Institute of Computer Science (IOCS), 2021)
The purpose of this research is to determine and analyze the impact of employee engagement and resistance to change on readiness for change with perceived organizational support as an intervening variable in change management at PT Pertamina (Persero). Readiness for change is an important thing that must be considered by companies when implementing change management. Aspects of human resources that affect readiness for change are employee engagement, resistance to change, and perceived organizational support. In this case, the researcher focuses on perceived organizational support variable as an intervening variable that links employee engagement and resistance to change with readiness for change. The population of this research were employees of PT Pertamina (Persero) with a sample of 154 people. The analytical method used descriptive statistical analysis and factor description analysis using SPSS V.23 and SmartPLS 3.0 software. The results showed that employee engagement and resistance to change have a positive and negative impact on perceived organizational support; employee engagement and perceived organizational support have no impact on readiness for change; resistance to change has a negative impact on readiness for change; employee engagement and resistance to change have no impact on readiness for change with perceived organizational support as intervening variable.